Optimizing Maleic Anhydride Production from Benzene's Cost by Preheating Inlet Air in Fired Heater and Modifying Distillation Column Operating Condition - Rongkang, Cornellius Powellnandus; Putri, Inayah S.; Kartawidjaja, Jason H.; Lestari, Putri Dwi A. (Journal of Chemical Engineering Research Progress, 2024)
The need for materials with superior properties from two different ingredients has recently attracted industries. Maleic anhydride or C4H2O3 is an intermediate product often used to mix materials with distinct characteristics. One way to produce maleic anhydride is by reacting benzene and air. Unfortunately, the production of maleic anhydride is classified as energy-consuming due to the plant equipment used such as fired heaters and distillation columns for the production. In this process modification, optimization is carried out on the fired heater by using the residual heat from combustion as an energy source for the preheating of incoming air. In addition, optimization was also carried out on the distillation column by changing the operating variables, especially the reflux ratio and column temperature.  Simulations were carried out using Aspen HYSYS V11 and comparisons were made between the energy required and the profit obtained from the original process to the modified process. The simulation results showed a reduction in energy cost by 0.771% on the fired heater and an increase in profit by 47.47% on the distillation column. Therefore, this modification reduces the energy cost while maximizing the profit made from maleic anhydride production using benzene and air. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).